Is first-trimester HbA1c useful in the diagnosis of gestational diabetes?. (November 2017) - Benaiges, David; Flores-Le Roux, Juana A.; Marcelo, Irene; Mañé, Laura; Rodríguez, Marta; Navarro, Xavier; Chillarón, Juan J.; Llauradó, Gemma; Gortazar, Lucia; Pedro-Botet, Juan; Payà, Antonio
Highlights: 1 st trimester HbA1c determination is an attractive choice for GDM screening. 1 st trimester HbA1c does not have sufficient power to diagnose GDM. The use of higher and lower HbA1c thresholds could simplify the diagnostic process. Abstract: Aims: To evaluate the usefulness and efficacy of first-trimester HbA1c in the diagnosis of gestational diabetes (GDM). Methods: Prospective observational of consecutive pregnant women. All women had a first-trimester HbA1c determination and GDM screening at 24–28 weeks of pregnancy using a two-step approach. A ROC curve was drawn to determine the sensitivity and specificity of HbA1c in detecting GDM and a rule-in rule-out diagnostic algorithm was proposed. The cost of the proposed algorithm was calculated. Results: 152 (13.1%) of 1195 women were diagnosed of GDM. The area under the ROC curve for HbA1c to detect GDM was 0.679 (95%CI 0.631–0.727). A rule-out threshold for HbA1c of 4.8% (29 mmol/mol) had 96.7% sensitivity (95%CI 93.9–99.5), 10.1% specificity (95%CI 8.3–12.0) and a negative predictive value of 95.3% (95%CI 91.3–99.3). A rule-in value of 5.6% (38 mmol/mol) had a positive predictive value of 31.6% (95%CI 24.4–38.9), 89.3% specificity (95%CI 87.4–91.2) and 32.9% sensitivity (95%CI 25.4–40.4). The low positive predictive value of the rule-in threshold precludes its use for GDM diagnosis, but could be used to identify women at high risk of GDM in whom the diagnosis can be established using a one-step approach. The overall saving of the proposed algorithm would be 6.5% of the total cost with the standard strategy. Conclusions: A first-trimester HbA1c does not have sufficient sensitivity or specificity to diagnose GDM, although the use of a higher and lower threshold could simplify the diagnostic process by reducing the number of oral glucose tolerance test, associated costs and patient inconvenience.